Comparision of family functions and personality patterns of male alcohol dependence patients with their wifes - Demirbaş, Hatice; Özgür İlhan, İnci and B. Doğan, Yıldırım (Journal of Dependence, 2009)
Objective: The aim of this study is to compare the family functions and personality traits of male alcohol dependent inpatients and their wifes. Methods: The sample consisted of 164 persons who were 82 alcohol dependent inpatients and their wifes (s=82) who have’nt alcohol and substance dependence from the Alcohol and Substance Treatment Unit, Department of Psychiatry of Ankara University. The Minnesota Multiphasic Personality Inventory (MMPI) and Family Assesment Device (FAD) were administered to all subjects. Age was controlled with Covariance Analysis. FAD scores were compared and common MMPI profile was drawed. Resuts: There was a statistical differences between scores of Roles, Affective Involvement and General Functions of Subscales of FAD (respectively F=8.646; p=0.004, F=4.440; p=0.037, F=8.916; p=0.003). It has been found that they have higher mean scores than 2.00 points which alcohol dependent patients have Roles, Affective Responsiveness and Affective Involvement, their wifes have all subscales of FAD. Depression subscale of MMPI common profile was higher in alcohol dependent patients and Masculinite-Feminite subscale of MMPI common profile was higher in their wifes. Conclusion: It was point out that wifes evaluate family functions as unhealthy than their husbands. We can say that wifes evaluation about family functions is relation with their personality patterns than husbands personality patterns. So that family interventions are important in treatment of alcohol dependent patients.